The relationship between motivations factors and online shopping participation among student in University Malaysia Pahang - Afikah, Abd Rahman @ Othman (2016)
In the era of globalization, electronic marketing is a great revolution. Over the last decade maximum business organizations are running with technological change. Online shopping is the use of technology for better marketing performance. And retailers are devising strategies to meet the demand of online shoppers. This research is carried out to study the relationship between motivation factors and online shopping participation among University Malaysia Pahang students . The objective of this research is to identify the dominant factor that influence online shopping participation and to determine the relationship between the motivation factors and online shopping participation. Three faculty from University Malaysia Pahang which is FIM, FTeK and FKKSA was selected as a scope for this study. Participation randomly selected final year student from these three faculty are the respondent to answer the questionnaire in this study.The participants are 217 randomly selected from different gender, faculty and so on. The result showed that perceived ease of use (independent variable) and online shopping participation (dependent variable)have a strong relationship between perceived usefulness and perceived risk. The correlation showed that perceived ease of use and online shopping participation have the highest correlation compared to perceived usefulness and perceived risk. It’s mean that the perceived ease of use is the dominant factor to influence online shopping participation.